Targeted drug screening for autism based on Cav1.2 calcium ion channel. - Chao Liu (PLoS ONE)
This study presents a targeted virtual drug screening approach for autism spectrum disorder (ASD), focusing on Cav1.2 calcium ion channels as potential therapeutic targets. ASD is a complex neurodevelopmental disorder characterized by impairments in social communication and behavior, with genetic factors playing a significant role. Cav1.2 channels have been implicated in the pathophysiology of ASD due to their role in regulating neuronal excitability and synaptic transmission. We employed computational methods to virtually screen a large database of compounds for their potential to modulate Cav1.2 channel function. Molecular docking simulations were used to identify potential Cav1.2 inhibitors, followed by pharmacokinetic modeling to assess drug-like properties. Molecular dynamics (MD) simulations were performed to evaluate the interactions of the top candidates with Cav1.2, and Molecular Mechanics/Poisson-Boltzmann Surface Area (MM/PBSA) analysis was employed to predict binding free energies. This approach identified several promising drug candidates, including ZINC000828320609, which exhibited strong binding affinity to Cav1.2, favorable pharmacokinetic properties, and no predicted toxicity. The virtual screening results provide a solid foundation for further experimental validation and potential drug development for ASD, offering a novel and efficient strategy to target Cav1.2 channels in the treatment of this complex disorder.